(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article reveals: factors necessary for the implementation of a quality system for educational activities, principles of monitoring:, essence of control, control circuit ,comparative capabilities of various forms of control.